The PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN IPHONE - BORU PURBA SIGUMONRONG, NATASHA RANI; GANDHIADI, G.K.; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 13 No 2 (2024)DO - 10.24843/MTK.2024.v13.i02.p449, 2024)
The mechanical advances of this cutting-edge time have significantly affected the manner in which individuals live, the most significant of which is in the part of communication. Handheld phones are communications devices that are being used today. The large number of customers' demands for smart phones due to the advantages of the features they possess make companies compete to be far superior to their rivals. The examination is pointed toward taking a gander at the impact of brand picture and item quality on iPHONE buy choices in Denpasar City. The method used is a partial least square with three latent variables in particular brand image, product quality, and purchase decision. The results obtained are brand image & product quality effect on the iPHONE purchase decision in Denpasar city. Brand image and product quality can explain or affect iPHONE purchase decisions by  percent.